1998
DOI: 10.1590/s1516-89131998000300016
|View full text |Cite
|
Sign up to set email alerts
|

Uso da taxocenose de peixes como indicadora de degradação ambiental no rio Paraíba do Sul, Rio de Janeiro, Brasil

Abstract: An adaptation of index of biotic integrity (IBI) was performed for the first time in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
(8 reference statements)
0
8
0
2
Order By: Relevance
“…According to Karr (1981), Araújo (1998) and Araújo et al (2003) the analysis of the trophic structure of a given fish community is an interesting tool for evaluation of environmental degradation. Karr (1981) and Araújo (1998) cited that an area can be analyzed using three major criteria: the proportions of omnivorous and insectivorous species in the environment and the presence of top piscivores. Karr (1981) and Araújo (1998) mentioned a strong negative correlation between the proportion of omnivorous and insectivorous species in disturbed environments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Karr (1981), Araújo (1998) and Araújo et al (2003) the analysis of the trophic structure of a given fish community is an interesting tool for evaluation of environmental degradation. Karr (1981) and Araújo (1998) cited that an area can be analyzed using three major criteria: the proportions of omnivorous and insectivorous species in the environment and the presence of top piscivores. Karr (1981) and Araújo (1998) mentioned a strong negative correlation between the proportion of omnivorous and insectivorous species in disturbed environments.…”
Section: Resultsmentioning
confidence: 99%
“…Karr (1981) and Araújo (1998) cited that an area can be analyzed using three major criteria: the proportions of omnivorous and insectivorous species in the environment and the presence of top piscivores. Karr (1981) and Araújo (1998) mentioned a strong negative correlation between the proportion of omnivorous and insectivorous species in disturbed environments. In our study we found a high abundance of omnivorous species, however we also found a high abundance of insectivorous species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Entre os mais frequentes fatores estudados em sistemas lóticos estão aqueles relacionados ao declínio da qualidade química da água (e.g., pH, oxigênio dissolvido, nitrato, amônia e fosfato), perda física do habitat (e.g., largura e integridade da vegetação ripária, tipos de substrato, e diversidade de mesohabitats), e declínio da integridade biótica (e.g., presença de espécies exóticas, tolerantes ou reofílicas) (Karr & Chu 1999). Karr (1981), Fausch et al (1990), Araújo (1998a, b), Bruschi Jr. et al (2000, Schiemer (2000) e Araújo et al (2003) utilizaram a comunidade de peixes como indicadores de qualidade da água em programas de monitoramento ambiental.…”
unclassified